Curricular Coherence of Transversal Competences - Vass, Vilmos (Autonomy and Responsibility Journal of Educational Sciences, 2022)
This article examines the curricular coherence of transversal competences, with a special regard on the “NCC-process”. Introducing the context of the topic, development of work- and life-related key competences appear with a growing demand in the world of work. The paper outlines the major results of the OECD DeSeCo project and the EU Framework of Key Competences. Examining the relationship and coherence among key competences we may conclude that they result in scientifi c and educational practice as well. The article analyses the two- and threedimensional structure of curriculum development according to the changing strategy and structure of the Hungarian National Core Curriculum. These structures enable delineation of feasible directions and fi elds of integration and implementation of transversal competences.